There Is More Than Meets the Eye: Success Stories of a Visually Impaired Student and a Lecturer - Delport, Danri Hester (INKLUSI, 2021)
Although Higher Education Institutions have come a long way in including students with disabilities, many students still experience exclusion or "otherness" among their abled peers. Currently, there is a gap in research where the focus is on the abilities and success stories of such individuals rather than their disabilities, the barriers they face, or the adjustments made to meet their needs. This research aims to share the success stories of a visually impaired student and his visually impaired lecturer at a South African University. Semi-structured, in-depth individual interviews were used as collection instruments where after the data was analyzed. The appreciation for friends outweighed the physical barriers. Through perseverance and hard work, the disabled student proved her teacher wrong by successfully entering university and completing her Ph.D.. Both participants looked beyond their limitations and realized their capabilities. [Meskipun usaha untuk mewujudkan perguruan tinggi inklusif sudah dilakukan sejauh ini, tetapi banyak mahasiswa difabel yang masih merasakan ‘keberbedaan’ dirinya dari mahasiswa lain. Inklusi penyandang disabilitas harus mengarah pada peningkatan partisipasi dalam tatanan yang menghasilkan siswa, teman, atau guru terbaik. Saat ini, ada kesenjangan dalam penelitian yang fokusnya adalah pada kemampuan dan kisah sukses individu tersebut daripada disabilitas mereka, hambatan yang mereka hadapi, atau penyesuaian yang dilakukan untuk memenuhi kebutuhan mereka. Penelitian ini bertujuan untuk berbagi kisah sukses seorang mahasiswa tunanetra sekaligus dosen tunanetranya di Universitas Afrika Selatan. Melalui ketekunan dan kerja keras, para difabel dalam tulisan ini membuktikan apa yang dianggap tidak mungkin. Kedua subyek melampaui keterbatasan mereka dan menyadari kemampuan mereka.]